2020
DOI: 10.7717/peerj.10175
|View full text |Cite
|
Sign up to set email alerts
|

Testing the short-and long-term effects of elevated prenatal exposure to different forms of thyroid hormones

Abstract: Maternal thyroid hormones (THs) are known to be crucial in embryonic development in humans, but their influence on other, especially wild, animals remains poorly understood. So far, the studies that experimentally investigated the consequences of maternal THs focused on short-term effects, while early organisational effects with long-term consequences, as shown for other prenatal hormones, could also be expected. In this study, we aimed at investigating both the short- and long-term effects of prenatal THs in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(39 citation statements)
references
References 86 publications
3
35
1
Order By: Relevance
“…Birds as oviparous vertebrates are widely used for the study of hormone functions on growth and development of the embryo (Groothuis and von Engelhardt, 2005), because the egg represents a closed system almost independent from maternal control once laid. The effects of the hormonal axes on growth, development, and aging can be tested by direct injection, e.g., of thyroid hormones into eggs (Sarraude et al, 2020). The latter increased telomere lengths in collared flycatchers and it was hypothesized that prenatal hormone exposure by this mechanism might set the aging clock in birds (Stier et al, 2020).…”
Section: Birds Birds (Aves)mentioning
confidence: 99%
“…Birds as oviparous vertebrates are widely used for the study of hormone functions on growth and development of the embryo (Groothuis and von Engelhardt, 2005), because the egg represents a closed system almost independent from maternal control once laid. The effects of the hormonal axes on growth, development, and aging can be tested by direct injection, e.g., of thyroid hormones into eggs (Sarraude et al, 2020). The latter increased telomere lengths in collared flycatchers and it was hypothesized that prenatal hormone exposure by this mechanism might set the aging clock in birds (Stier et al, 2020).…”
Section: Birds Birds (Aves)mentioning
confidence: 99%
“…The experiment by Sarraude et al (2020) investigated the effects of prenatal thyroid hormones injections to quails on a number of traits (e.g., egg hatching success, embryonic development, and offspring growth). The eggs were injected with the prohormone ( ), its active metabolite ( ), a combination of both and ( ), or none (i.e., control eggs, CO).…”
Section: Illustrative Datamentioning
confidence: 99%
“… Sarraude et al (2020) fitted a number of candidate models to the growth in body mass of quails using a nonlinear generalized additive mixed model. For illustration, we consider the model, henceforth referred to as the generalized additive model, that incorporated a temporal autocorrelation of the residuals using an autoregressive moving average ARMA(1, 1) model; a random intercept for the mother’s identity; treatment group, and sex as fixed effects; and thin plate regression spline for the age of the offspring varied by sex.…”
Section: Data Visualizationmentioning
confidence: 99%
“…Maternally transferred thyroid hormones play crucial roles in the development of the central nervous system (Darras, 2019) and several other tissues and organs (e.g., muscles, heart, eye, bones; McNabb and Darras, 2015). In addition, recent studies in birds have shown that physiological variation in prenatal THs can affect hatching success, growth and metabolism (Hsu et al, 2017;Hsu et al, 2019;Ruuskanen et al, 2016;Sarraude et al, 2020a).…”
Section: Journal Of Experimental Biology • Accepted Manuscriptmentioning
confidence: 99%